BSF Maggot Cultivation Training as a Sustainable Solution for Organic Waste and Affordable Animal Feed in Cisalak Village - Abdul Hamid; Neli Purwanti; Sutopo S (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
Cisalak Village has various potentials, one of which is in the livestock sector. In this sector, there are various types of cultivation businesses, such as chicken, catfish, patin fish, and other fish for consumption. However, farmers often face challenges in the form of increasing prices of animal feed. Both chicken and fish require large amounts of feed before they can be harvested, so that the spike in feed prices is an obstacle to the sustainability of livestock businesses in the village. This PKM program aims to provide training on BSF maggot cultivation as a solution in managing organic waste as well as an alternative to animal feed in Cisalak Village, Cisarua, Sumedang. The method used in this PKM is a socialization approach. This training activity was carried out well on March 9, 2026 and received a positive response from the local community. The enthusiasm of the residents was very high in participating in the series of activities, because this training offers a solution to the problem of expensive animal feed. The sustainability of this program depends on the consistency of the community in cultivating BSF maggots, so that the availability of animal feed is maintained and the price of feed is more affordable.